Meditation and psychedelics facilitate similar types of mystical, psychological, and philosophical-existential insights predictive of wellbeing: a qualitative-quantitative approach - Jylkkä, Jussi; Väyrynen, Hilla; Lin, Enyu; Walldén, Catharina; Krabbe, Andreas; Kähönen, Juuso; Sikka, Pilleriin (Elsevier BV, 2025)
Both psychedelic substances and meditation have been proposed to facilitate personally meaningful and transformative experiences, with insights playing a central role. However, previous research has mainly relied on questionnaires, limiting the range of insights that can be identified. In this study, we recruited participants who provided narrative reports of insights in personally meaningful psychedelic (n = 147) or meditation (n = 66) experiences. Psychedelic experiences were facilitated both by classic (e.g., LSD, psilocybin, DMT) as well as non-classic (e.g., MDMA, ketamine, cannabis) psychedelics. Qualitative analysis revealed three main insight themes: Mystical-type (subclasses Unity, Metaphysical, and Other), Psychological (subclasses Metacognitive, Value, and Compassion), and Philosophical-existential (subclasses Purpose, Value, and Other). Mystical-type insights were more frequent in reports of meditation experiences, while value insights were more common in psychedelic reports. Otherwise, the reported insights were highly similar across the two types of reports, and only minor differences were observed between classic and non-classic psychedelics. Regression analyses indicated that metacognitive and value insights were positively associated with perceived improvements in positive affect, while mystical-type insights predicted increased meaning in life. These findings suggest that both psychedelic substances and meditation can facilitate a broad range of insights that are not fully captured by existing questionnaires. The results highlight similarities between psychedelic and meditation experiences supporting the notion that transformative experiences are not exclusive to classic psychedelics but can be facilitated through various means.